Nocturnal blood pressure patterns and cardiovascular outcomes in patients with masked hypertension. Issue 9 (29th July 2018) - Presta, Vivianne; Figliuzzi, Ilaria; D'Agostino, Michela; Citoni, Barbara; Miceli, Francesca; Simonelli, Francesca; Coluccia, Roberta; Musumeci, Maria Beatrice; Ferrucci, Andrea; Volpe, Massimo; Tocci, Giuliano
Abstract : Masked hypertension (MHT) is characterized by normal clinic and above normal 24‐hour ambulatory blood pressure (BP) levels. We evaluated clinical characteristics and CV outcomes of different nocturnal patterns of MHT. We analyzed data derived from a large cohort of adult individuals, who consecutively underwent home, clinic, and ambulatory BP monitoring at our Hypertension Unit between January 2007 and December 2016. MHT was defined as clinic BP <140/90 mm Hg and 24‐hour BP ≥ 130/80 mm Hg, and stratified into three groups according to dipping status: (a) dippers, (b) nondippers, and (c) reverse dippers. From an overall sample of 6695 individuals, we selected 2628 (46.2%) adult untreated individuals, among whom 153 (5.0%) had MHT. In this group, 67 (43.8%) were nondippers, 65 (42.5%) dippers, and 21 (13.7%) reverse dippers. No significant differences were found among groups regarding demographics, clinical characteristics, and prevalence of risk factors, excluding older age in reverse dippers compared to other groups ( P < 0.001). Systolic BP levels were significantly higher in reverse dippers than in other groups at both 24‐hour (135.6 ± 8.5 vs 130.4 ± 6.0 vs 128.2 ± 6.8 mm Hg, respectively; P < 0.001) and nighttime periods (138.2 ± 9.1 vs 125.0 ± 6.3 vs 114.5 ± 7.7 mm Hg; P < 0.001). Reverse dipping was associated with a significantly higher risk of stroke, even after correction for age, gender, BMI, dyslipidemia, and diabetes (OR 18.660; 95% IC [1.056‐33.813]; P = 0.046). MHT with reverse dipping status was associated with higher burden of BP and relatively high risk of stroke compared to both dipping and nondipping profiles, although a limited number of CV outcomes have been recorded during the follow‐up.